Guideline for Character Design: A Case Study of ‘Character Design Challenge’ - Hetayothin, Chanya (Asian Creative Architecture, Art and Design, 2021)
This creative research aims at contributing to knowledge in character design, using character design contest ‘Character Design Challenge’ as a case study. The objectives are: 1) To search for guideline for character design; 2) To design characters. The research method employs in-depth interviews with twelve experts, aged between 25-45 years. Nine of them including designers, art directors, head of story, university instructor have at least ten years of character design experience in the industry. The other three are intermediate skilled designers with at least three years of work experience. The finding shows that guideline for character design consists of the four components: 1) Developing Character – besides story, character profile, archetype and character style, designer needs to think inside-out as being a character in order to better understand the character; 2) Character Expressions – apart from body language and facial expressions, designer should pay attention to viewing angles to enhance the visual interest of the characters. 3) Design Elements and Principles – since they have an important role in character stylization, designer needs to find balance in stylizing characters and choose design elements and principles in relation to character’s personality so the design can effectively present the character’s physical attributes; 4) Design Process - good research process brings new ideas to design. Five pieces of character design work demonstrate that clarity in communication and character’s attractiveness are crucial. Once the four components work together effectively, clarity in communication and character’s attractiveness occur. The research knowledge can be adopted as a guideline for character design.